2010
DOI: 10.1111/j.1365-2893.2010.01373.x
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-four weeks of pegylated interferon plus ribavirin effectively treat patients with HCV genotype 6a

Abstract: The optimal duration of treatment and expected response rate for hepatitis C virus genotype (HCV-6)-infected patients have not been determined. Our aims were to determine the treatment outcome with pegylated interferon (PEG-IFN) plus ribavirin for HCV-6a-infected patients at Southwest Hospital and assess the association of the on-treatment virological response with the sustained virological response (SVR). Medical records were reviewed retrospectively. Twenty-two HCV-6a-infected patients were treated for 24 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 22 publications
5
21
0
Order By: Relevance
“…Both of the mutations showed association with viral clearance in SVR patients. Association of mutations outside PKR with treatment outcome have also been reported by Zhou et al, [28] particularly in genotype 1b. El-Shamy et al [29], have identified a region downstream to ISDR named as IFN/Ribavirin resistance determining region (IRRDR) in genotype 1b.…”
Section: Discussionsupporting
confidence: 59%
“…Both of the mutations showed association with viral clearance in SVR patients. Association of mutations outside PKR with treatment outcome have also been reported by Zhou et al, [28] particularly in genotype 1b. El-Shamy et al [29], have identified a region downstream to ISDR named as IFN/Ribavirin resistance determining region (IRRDR) in genotype 1b.…”
Section: Discussionsupporting
confidence: 59%
“…Six trials assessed treatment response in patients infected with HCV-6 compared with those infected with HCV-1 [18,19,21,27,29,30]. Among these, 3 were direct comparisons of response to antiviral therapy by HCV-6 versus HCV-3 and/or HCV-2 patients.…”
Section: Resultsmentioning
confidence: 99%
“…The modified process employed for study search and selection is summarized in figure 1. After the titles were screened and abstracts read, 193 studies were removed based on exclusion criteria and 14 potentially eligible articles included [17,18,19,20,21,22,23,24,25,26,27,28,29,30]. Among these studies, some studies were only included on the treatment efficacy of PEG-IFN+RBV for HCV-6 in a previous study [31].…”
Section: Resultsmentioning
confidence: 99%
“…The geographic proximity to Southeast Asia and presence of drug trafficking and use likely explains route of entry of genotype 6a into the Guangdong province. The [46]. In vitro studies on efficacy of novel protease inhibitors (PI) on genotype 6a have also demonstrated good response [47], and a limited but promising U.S.-based phase 2 clinical trial on genotype 6 patients demonstrated all five HCV genotype 6 patients enrolled achieving SVR on 24 weeks of sofosbuvir in combination with peg-interferon and ribavirin [48].…”
Section: Discussionmentioning
confidence: 99%